2017
DOI: 10.18632/oncotarget.16747
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serologic markers of HPV 16 infection are associated with local recurrence in patients with oral cavity squamous cell carcinoma

Abstract: Human papillomavirus (HPV) infections predict mortality in Taiwanese patients with oral cavity squamous cell carcinoma (OCSCC). To address their prognostic significance for local recurrence (LR), in this retrospective cohort study we investigated different serologic and molecular markers of HPV 16 infection in 85 consecutive patients with primary OCSCC who received standard treatment and had their sera stored before treatment. Resected tumor specimens were examined with PCR-based assays for HPV 16 E6/E7 mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 79 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…This is partially based on the finding that in contrast to CxCa, antibodies to HPV16 E6 and E7 are prospective markers for OPC that can be detected 10þ years prior to diagnosis [12,13]. In OPC, antibody presence or their levels at the time of diagnosis [14][15][16][17][18][19] as well as antibody kinetics during patient follow-up after primary tumour treatment [15,16,20] have been investigated as markers for prediction of treatment success (i.e. complete tumour removal) and the likelihood of disease recurrence.…”
mentioning
confidence: 99%
“…This is partially based on the finding that in contrast to CxCa, antibodies to HPV16 E6 and E7 are prospective markers for OPC that can be detected 10þ years prior to diagnosis [12,13]. In OPC, antibody presence or their levels at the time of diagnosis [14][15][16][17][18][19] as well as antibody kinetics during patient follow-up after primary tumour treatment [15,16,20] have been investigated as markers for prediction of treatment success (i.e. complete tumour removal) and the likelihood of disease recurrence.…”
mentioning
confidence: 99%
“…There are variations among included studies in methods for HPV detection, HPV prevalence, HPV types detected, as well as the minimum and maximum follow‐up period. The study design included 22 cohort studies published from 1996 to 2020 that were all retrospective 9,13–16,23–39 (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…For the primary outcomes, there were 13 studies that provided the data in OS for HPV-positive and HPV-negative OSCC patients, 15,16,24,25,28,[31][32][33][34][36][37][38][39] followed by 9 studies that reported DSS, [13][14][15][27][28][29]31,32,37 and 8 studies documented DFS. 9,15,23,[26][27][28]34,38 While in secondary outcomes, there were 5 studies that reported LC rate for HPV-positive and HPV-negative OSCC patients, 15,26,28,30,35 followed by 4 studies that reported RC rate 14,24,26,37 and 5 studies that reported DC rate. 15,26,28,30,37 The scores of quality for included studies were varied, with the mean of score of 6.8 (ranging from 5-8) (Table II).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The impact of HPV has been investigated in oral cancer in the last decades and the association with OPSCC, and OSCC has been well established (17,18). The longitudinal studies have not yet shown the predictive value of HPV-HR+ in development of oral cancer but a poor clearance of E7 antibody associated to HPV-16 are associated to OPSCC and OSCC recurrence (27,28). As an increase in oral cancer associated with HPV has been observed, the study of HPV infection in early stages has been a focus of attention in recent years (29,30).…”
Section: Discussionmentioning
confidence: 99%